Effects of social support on music performance anxiety among university music students: chain mediation of emotional intelligence and self-efficacy - Huawei, Zhang; Jenatabadi, Hashem Salarzadeh (Frontiers in Psychology, 2024)
The primary goal of this research is to investigate the relationship between social support and music performance anxiety in the context of social cognitive theory and stimulus-organization-response theory among music university students in China. The study involved both postgraduate and undergraduate students. The suggested framework consisted of three independent variables: parental support, teacher support, and peer support, two mediators: emotional intelligence and self-efficacy, and one dependent variable: music performance anxiety. A survey of 483 students was undertaken, and the data was analyzed using path analysis and structural equation modeling. The study discovered that all three forms of parental, teacher, and peer support were positively associated to both self-efficacy and emotional intelligence, with postgraduate students experiencing the strongest effects. Furthermore, self-efficacy and emotional intelligence had a negative significant effect on music performance anxiety, with the association being stronger among postgraduate students. Finally, self-efficacy and emotional intelligence emerged as significant mediators of the relationship between social support and music performance anxiety. These results add to our knowledge of the mechanisms by which social support influences music performance anxiety.